Features of the training process of handball players of higher qualification between rounds in the competitive period - Tyshchenko, V. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: the technology of preparation of athletes in accordance with the requirements of the system approach. Team management methodology disclosed in terms of the training process in the competitive period between rounds of the regular championship of Ukraine. Material: the experiment involved 85 athletes aged 18-32 years.